The Distribution of the Frog Eleutherodactylus johnstonei (Amphibia:Eleutherodactylidae) in Trinidad, West Indies - Manickchan, Shiva A.; Starr, Christopher K.; Ramjohn, Carol; Mahabir, Srishti V.; Mahabir, Kevin; Mohammed, Ryan S. (My University, 2012)
Eleutherodactylus johnstonei is an invasive anuran of Trinidad, West Indies. Monitoring the spread has shown that its local range is the north-west of Trinidad. E. johnstonei is increasing in population size and is increasing its local range by expanding into disturbed habitats. No immediate ecological threat has been identified. Previous studies on high amplitude callers suggest that E. johnstonei has the potential to become a pest in urban residential areas due to its loud mating calls. It is likely that E. johnstonei has become a permanent part of Trinidad’s biodiversity and its calls would become common in many more suitable disturbed areas in Trinidad.